Criminal Characterization of Appropriation and Embezzlement and Their Separation - Mailashvili, Jumber (European Scientific Journal, ESJ, 2017)
During the implementation of the study we will review the definition set forth following the amendments and additions made by the Parliament of Georgia on October 23, 2008 in the Article 182 (appropriation or embezzlement) of the Criminal Code of Georgia. After the amendments in legal literature and judicial practice, there are critical remarks with regard to the norm disposition. In the above study I will refer to the qualification issues of appropriation or embezzlement in terms of both similarity and separation. We aim to examine and highlight the main problems that can be created in the activities of investigative and judicial bodies unless the Parliament of Georgia includes relevant amendments and additions in the Article 182 of the Criminal Code of Georgia. I will provide hypothetical cases and comparison examples and try to justify the legal qualification with regard to the Article for discussion. I will try to highlight the main issues that, during the application of the norm, will rise a problem in judicial practice due to the vagueness of the norm. In the last part of the paper, I will provide the similarities and differences of appropriation and embezzlement. As well as the analysis of the issues that create the problem during the qualification of the action.